Joy of Ugly Feelings: Korean “Bad Taste” Webtoons as a Case Study - Hyesu Park (Studies in 20th & 21st Century Literature, 2017)
Cognitive narratology has contributed significantly to our understanding of reading fiction, namely, what happens when we read and why we read at all. According to scholars such as Lisa Zunshine, Alan Palmer, and George Butte, we have an evolved craving to read the minds of others, and reading fiction ultimately is a busy act of reading and misreading minds of characters in the storyworld. My paper questions this cognitivist belief by using Korean “bad taste” webtoons (online comics using violent verbal and visual for amusement) as a case study. I discuss ways in which the absence of readable minds and empathy as well as technological properties of these webtoons debunk the myths of mind reading and readable minds and their impact on immersive reading experience. Instead they allow for what neurologists call “detachment manipulation condition” and the concurrence of mixed feelings (negative and positive), leading to a mode of reading that works the best when readers remain irrelevant to and detached from the fictional world that they witness, but do not experience. Overall, this paper reconsiders what constitutes immersion in a fictional world, the role of mind reading and empathy in fiction, and the intersection between narrative and technology among other things.
Keywords: Webtoons; Mind Reading; Empathy; Cognitive Narratology; Emotions